Migration and labour market outcomes in OECD countries - Jean, Sébastien (OECD Publishing, 2010)
Immigration pressures are increasing in most OECD countries. This article investigates the consequences of immigration for natives' labour market outcomes, as well as issues linked to immigrants' integration in the host country labour market. Changes in the share of immigrants in the labour force may have a distributive impact on natives' wages, and a temporary impact on unemployment. However, labour market integration of immigrants (as well as integration of second-generation immigrants both in terms of educational attainments and of labour market outcomes) remains the main challenge facing host economies. In both cases, product and labour market policies have a significant role to play in easing the economy's adjustment to immigration